Subsurface Engineering Induced Fermi Level De‐pinning in Metal Oxide Semiconductors for Photoelectrochemical Water Splitting. (24th January 2023) - Wang, Jun; Ni, Ganghai; Liao, Wanru; Liu, Kang; Chen, Jiawei; Liu, Fangyang; Zhang, Zongliang; Jia, Ming; Li, Jie; Fu, Junwei; Pensa, Evangelina; Jiang, Liangxing; et al.
Abstract: Photoelectrochemical (PEC) water splitting is a promising approach for renewable solar light conversion. However, surface Fermi level pinning (FLP), caused by surface trap states, severely restricts the PEC activities. Theoretical calculations indicate subsurface oxygen vacancy (sub‐Ov ) could release the FLP and retain the active structure. A series of metal oxide semiconductors with sub‐Ov were prepared through precisely regulated spin‐coating and calcination. Etching X‐ray photoelectron spectroscopy (XPS), scanning transmission electron microscopy (STEM), and electron energy loss spectra (EELS) demonstrated Ov located at sub ∼2–5 nm region. Mott–Schottky and open circuit photovoltage results confirmed the surface trap states elimination and Fermi level de‐pinning. Thus, superior PEC performances of 5.1, 3.4, and 2.1 mA cm −2 at 1.23 V vs. RHE were achieved on BiVO4, Bi2 O3, TiO2 with outstanding stability for 72 h, outperforming most reported works under the identical conditions. Abstract : By means of universal subsurface oxygen vacancy strategy, the surface Fermi level de‐pinning in a series of metal oxide semiconductor are achieved while retaining the active defective structure. The completely splitted quasi Fermi level of holes and electrons induces enhanced open‐circuit photovoltage, providing sufficient driving force for charge transfer, to achieve robust photoelectrochemical water splitting.